2019
DOI: 10.1001/jamanetworkopen.2019.1851
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Postdonation Outcomes in US Living Kidney Donors Using Publicly Available Data Sets

Abstract: Key Points Question What are the postdonation outcomes of living kidney donors? Findings In this cohort study of 10 869 living kidney donors from the ImmPort open access data repository, 9558 individuals’ postdonation data were analyzed. Overall, 1406 living donors (14.7%) had postdonation events; the 4 most common events were hypertension, diabetes, proteinuria, and postoperative ileus, and most events that occurred more than 2 years after transplant were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…( 68) An additional clinical study on the safety of American living donors reported that 85.3% of donors could not be properly assessed due to the cessation of follow-up or lack of data. (69) This report also showed a high possibility that non-surgical adverse events occurred more than 2 years after donation. (69) Given the results of these studies, both the follow-up rate and period of the present study were su cient to show reliable results.…”
Section: Discussionmentioning
confidence: 70%
“…( 68) An additional clinical study on the safety of American living donors reported that 85.3% of donors could not be properly assessed due to the cessation of follow-up or lack of data. (69) This report also showed a high possibility that non-surgical adverse events occurred more than 2 years after donation. (69) Given the results of these studies, both the follow-up rate and period of the present study were su cient to show reliable results.…”
Section: Discussionmentioning
confidence: 70%
“…A significant proportion of LDKT donors (10%) developed low life satisfaction although 96% reported no regrets donating their kidneys at two years [48]. However, long term QOL assessment remains lacking, despite the fact that most non-surgical LDKT complications such as hypertension and diabetes only surface five years post-donation [49]. Therefore, more prospective studies on longer term psychological effects of LDLT and LDKT donors are warranted.…”
Section: Risk Factors For Adverse Mental Outcomes In Donorsmentioning
confidence: 99%
“…A curated data set, immTransplant, with postdonation outcomes for kidney living donors were derived from 20 clinical studies (clinical trials and observational studies) in ImmPort. 41 The availability of such data gives an opportunity to build a "trajectory map" for the sequence of events in a subset of living donors with a long-term follow-up post-donation. This approach retrospectively helps to investigate the patterns of surgical and nonsurgical conditions that may arise post-donation in living donors.…”
Section: Drug Development Toolsmentioning
confidence: 99%